Hydraulically Controlled Bottom Flow in the Orkney Passage - Eugene G. Morozov; Dmitry I. Frey; Oleg A. Zuev; Manuel G. Velarde; Viktor A. Krechik; Rinat Z. Mukhametianov (Water, 2022)
Supercritical hydraulically controlled overflow of Antarctic Bottom Water from the Weddell Sea has been observed in the Orkney Passage during field measurements in February 2022. The Orkney Passage is the main pathway for the densest layer of Antarctic Bottom Water flow from the Weddell Sea to the Scotia Sea. The bottom current overflows the sill across the passage and flows down from the crest of the sill at 3600 m deeper than 4000 m. The descending flow accelerates because of the difference in the height of the sill and its foot. An estimate of the Froude number of this flow was greater than unity. Near the foot of the slope the kinetic energy of the flow becomes insufficient to continue moving in this regime. The flow slows down, and strong mixing and warming of the bottom water occurs due to the exchange with the surrounding waters. This hydrodynamic phenomenon is called supercritical hydraulically controlled flow. However, the flow of bottom water continues further and eventually fills the abyssal depths of the Atlantic.